Gender Differences in Mate Selection: Evidence From a Speed Dating Experiment - Fisman, R.; Iyengar, S. S.; Kamenica, E.; Simonson, I. (Quarterly Journal of Economics, 2006)
We study dating behavior using data from a Speed Dating experiment where we generate random matching of subjects and create random variation in the number of potential partners. Our design allows us to directly observe individual decisions rather than just final matches. Women put greater weight on the intelligence and the race of partner, while men respond more to physical attractiveness. Moreover, men do not value women's intelligence or ambition when it exceeds their own. Also, we find that women exhibit a preference for men who grew up in affluent neighborhoods. Finally, male selectivity is invariant to group size, while female selectivity is strongly increasing in group size.